Evaluation of Clay-Based Binders and In-Feed Antimicrobials on Growth Performance and Biological Measurements in Nursery Pigs - Larissa L. Becker; Jordan T. Gebhardt; Mike D. Tokach; Robert D. Goodband; Joel M. DeRouchey; Jason C. Woodworth; Raghavendra G. Amachawadi; Ramya Kalam; Xiaorong Shi; T. G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 360 barrows (DNA 200 × 400; initially 14.2 ± 0.08 lb) were used in a 42-d growth study to evaluate clay-based binders or an in-feed antimicrobial on growth performance and biological measurements including fecal and blood analysis in nursery pigs. Pigs were weaned at approximately 21 d of age and randomly allotted to 1 of 4 dietary treatments in a completely randomized design. There were 5 pigs per pen and 18 replications per treatment. Dietary treatments were corn-soybean meal-based and fed in two phases from d 0 to 9 (phase 1) and 9 to 21 (phase 2) after weaning. Either Protek (0.40% of the diet; Nutriquest, Mason City, IA); Protect-8 Plus (0.10% of the diet; Essential Ag Solutions, Sioux Falls, SD); or Kavault (0.04% of the diet; Avilamycin; Elanco, Greenfield, IN) were added to the control diet to create the experimental treatments. A common phase 3 diet was fed to all pigs from d 21 to 42. Overall (d 0 to 42), pigs fed Kavault had increased (P<0.05) final BW, ADG, and ADFI compared to all other treatments. There was evidence that frequency of fecal scores with softer feces increased over time (P<0.001), with d 21 having the greatest frequency of diarrhea and soft feces. FecalEscherichia colicolony count was lower (P<0.001) on d 21 compared to d 9. For fecal myeloperoxidase (MPO), concentrations were lower (P<0.05) on d 21 compared to d 6 and 9. For fecal DM, pigs fed Kavault had decreased (P<0.05) DM percentage compared to all other treatments. Fecal DM percentage was higher (P<0.05) on d 6 and 9 compared to d 21. No differences (P>0.10) were observed across treatments for fecal scores, fecalE. colicolony count, fecal MPO or virulence genes associated withE. coli. Similarly, no differences (P>0.10) were observed across treatments for TNF-alpha and IL-6 blood assays. For IL-6, concentrations were greater (P<0.05) on d 9 compared to d 21. In summary, pigs fed Kavault had increased BW, ADG, and ADFI, compared to those fed the 2 clay-based additives or the control diet. There were no treatment effects on fecal score, fecal MPO, or blood measurements. However, we observed a day effect indicating that feces were softer and had less DM on d 21 compared to d 6 and 9. Additionally, fecalE. colicolony count and MPO had lower concentrations of d 21 compared to d 9. There was a strong negative correlation between fecal DM and score (P<0.001) on d 6, 9, and 21 indicating that as fecal DM increased, the score became closer to 0, representing a firmer fecal sample. Fecal DM on d 6 and fecal DM on d 9 were negatively correlated with ADG from d 0 to 9 meaning that as growth rate increased, fecal DM decreased.
Keywords: Binder; antimicrobial; nursery pig